Aspek Ritual pada Sistem Irigasi Subak sebagai Warisan Budaya Dunia - Wayan Windia; Sumiyati Sumiyati; Gede Sedana (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
AbstractThis paper introduces some ritual activities performed by individual farmer within subak system. Subak is farmers managed irrigation system which has an irrigation water source irrigated to certain compound of rice fields and hasa particular temple. The ritual ceremony is a part of important thing of Tri Hita Karana (THK) implementation, namelyparhyangan aspect presenting the harmonious relationship between farmer and the God. The other components of THK are pawongan (the harmonious relationship among subak’s members) through the implementation of subak’s regulation (awig-awig); and palemahan presenting the harmonious relationship between farmer and environment through the rice field terrace maintenance. There are 16 activities of ritual ceremonies individually performed by farmer as subak’s member starting from the ritual of fetching irrigation water until the post-harvest ritual ceremony. A side from this, thereare also ritual ceremonies conducted by the all members at the subak level. Subak also has ritual ceremonies carried out together with the other subaks in the temples located near the dam, lake and others. These ritual activities constitute as acultural practices conducted by subak. Therefore, subak has been regarded as the keeper of Balinese culture by implementing THK, thus UNESCO has acknowledged subak asworld cultural heritage.